Preparation method of high-stability high-energy EMOFs material

CN117384390BActive Publication Date: 2026-11-03HUBEI INST OF AEROSPACE CHEMOTECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311558084.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-20
Publication Date
2026-11-03
Estimated Expiration
2043-11-20

AI Technical Summary

Technical Problem

Existing technologies cannot effectively improve the performance and application potential of EMOFs by changing their framework structure, and synthesizing new EMOFs with novel structures and properties is difficult and uncontrollable.

Method used

High-energy EMOFs materials with high energy stability were prepared by using high-energy explosives TKX-50 and NTO as high-energy molecular modifiers, mixing them with metal ion salts and nitrogen-rich azole ligands in a solvent, and then preparing them by adding strong acid solution and allowing them to stand. The physicochemical properties were adjusted while maintaining the framework structure.

Benefits of technology

This method improves the energy properties and stability of EMOFs materials while maintaining the integrity of the framework structure, giving them the potential to be used as heat-resistant and desensitizing explosives. It is also simple, safe and efficient to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117384390B_ABST
    Figure CN117384390B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of energetic materials, and particularly discloses a preparation method of a high-stability high-energy EMOFs material, which comprises the following steps: S01: raw materials are respectively added into solvents, and are stirred and heated until completely dissolved and filtered to obtain raw material solutions; the raw materials comprise metal ion salts, nitrogen-rich azole ligands and high-energy molecular regulators; the raw material solutions comprise metal ion salt solutions, nitrogen-rich azole ligand solutions and high-energy molecular regulator solutions; S02: the raw material solutions are mixed in a mixing order, stirred, and a strong acid solution is first added dropwise, constant-temperature stirring is carried out, and filtering is carried out to obtain a transparent mixed solution; S03: the clear transparent mixed solution is transferred into a reaction device, a strong acid solution is secondly added dropwise, then the reaction device is sealed in a constant-temperature oven, and standing is carried out, and the transparent crystals separated out are high-stability high-energy EMOFs materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of energetic materials technology, specifically to a method for preparing highly stable, high-energy EMOFs materials. Background Technology

[0002] Energetic metal-organic frameworks (EMOFs) are a class of coordination compounds with different dimensions and spatial structures, formed through molecular self-assembly driven by coordination interactions between polyazole-based energetic organic ligands and metal ions. As an important component of energetic materials, EMOFs have attracted widespread attention due to their stable geometric topology, designable energetic ligands, tunable detonation performance, and safety. From a chemical structure perspective, EMOFs are mainly composed of a single coordinating metal ion and a single organic energetic ligand. Currently, the primary method for adjusting their physicochemical properties is to prepare novel EMOFs by changing different single coordinating metal ions or single organic energetic ligands. However, for most EMOFs, changing the coordinating metal ion or organic energetic ligand does not guarantee the synthesis of EMOFs with entirely new structures and properties. Synthesizing new EMOFs with application potential is difficult and uncontrollable. Therefore, how to adjust the framework structure of EMOFs to improve their performance and applications is a pressing problem that needs to be solved. Summary of the Invention

[0003] To address the aforementioned problems, one objective of this invention is to provide a method for preparing highly stable and high-energy EMOFs materials. This method is simple, safe, and efficient, and effectively improves the energy properties and stability of EMOFs materials while maintaining the integrity of the original EMOFs material framework structure.

[0004] The technical solution adopted in this invention is: a method for preparing highly stable, high-energy EMOFs materials, comprising the following steps:

[0005] S01: Add the raw materials to the solvent separately, heat and stir until completely dissolved, filter, and obtain the raw material solutions respectively;

[0006] The raw materials include metal ion salts, nitrogen-rich azole ligands, and high-energy molecular modulators.

[0007] The raw material solution includes a metal ion salt solution, a nitrogen-rich azole ligand solution, and a high-energy molecular regulator solution.

[0008] S02: Mix the raw material solutions in the mixing order, stir, add strong acid solution dropwise for the first time, stir at constant temperature, filter, and obtain a clear and transparent mixed solution;

[0009] S03: Transfer the clear and transparent mixed solution to the reaction device, add a strong acid solution dropwise for the second time, then seal the reaction device in a constant temperature oven and let it stand. The precipitated transparent crystals are the high-stability, high-energy EMOFs materials.

[0010] Preferably, the metal ion salt includes one of Cu(NO3)2, Cu(BF4)2, CuSO4, Co(NO3)2, Co(BF4)2, CoCl2, Zn(NO3)2, Zn(BF4)2, ZnSO4, Fe(NO3)2, FeSO4, FeCl2, Ni(NO3)2, NiCl2, and their corresponding metal ion salt hydrates;

[0011] The concentration of the metal ion salt solution is greater than or equal to 1.5 mg·mL. -1 .

[0012] Preferably, the azole ligand is 4,4′-azo-1,2,4-triazole.

[0013] Preferably, the high-energy molecular modulator includes one of 5,5′-bitetrazole-1,1′-dioxohydroxyammonium salt and 3-nitro-1,2,4-triazol-5-one.

[0014] Preferably, the solvent is one of deionized water, methanol, ethanol, acetonitrile, acetone, ethyl acetate, and dichloromethane.

[0015] Preferably, the mixing sequence in step S02 is as follows: first, the metal ion salt solution and the nitrogen-rich azole ligand solution are mixed, and then a high-energy molecular regulator solution is added; the mixture is stirred at 30-70°C for 1-3 hours, and a strong acid solution is added dropwise for the first time, and the mixture is stirred at a constant temperature for 0.5-2 hours.

[0016] The settling conditions in step S03 are settling at 20-60°C for 7-14 days.

[0017] Preferably, the molar ratio of the metal ion salt solution to the azole ligand solution is 5:1 to 1:5;

[0018] The high-energy molecular regulator solution comprises less than or equal to 40 wt% of the total solution.

[0019] Preferably, the strong acid solution is one of 38% concentrated HCl, 98% concentrated H2SO4, and 68% concentrated HNO3.

[0020] Preferably, the amount of the first drop of strong acid solution is 1% to 10% of the total volume of the solution.

[0021] Preferably, the amount of the second drop of strong acid solution is 1 to 10 drops.

[0022] The beneficial effects of the above technical solution are as follows:

[0023] (1) This invention uses high-energy explosives to adjust the physicochemical properties of EMOFs materials. The operation is simple, safe and efficient. By taking advantage of the coordination interaction between high-energy explosives and the metal central atoms of EMOFs materials, the chemical structure of EMOFs materials is modified and the spatial structure is adjusted, thereby achieving the adjustment of the physicochemical properties of EMOFs materials.

[0024] (2) The high-stability, high-energy EMOFs material obtained by the method of the present invention after adjustment of physical and chemical properties can maintain the integrity of the original EMOFs material skeleton structure, and at the same time effectively improve the energy characteristics and stability of the EMOFs material.

[0025] (3) The present invention uses high-energy explosives TKX-50 and NTO as high-energy molecular modifiers respectively. When the dosage is different, the physical and chemical properties of the obtained EMOFs materials are significantly different.

[0026] (4) The high-stability high-energy EMOFs materials prepared by using high-energy explosives TKX-50 and NTO as high-energy molecular modifiers described in this invention have the potential to be used as heat-resistant and desensitizing explosives. Attached Figure Description

[0027] Figure 1 The coordination environment diagram of EMOF-1 material in Comparative Example 1 is obtained by X-ray single-crystal diffraction (SXRD).

[0028] Figure 2 The image shows a scanning electron microscope (SEM) image of the EMOF-1 material in Comparative Example 1.

[0029] Figure 3 This is a scanning electron microscope (SEM) image of the EMOF-1@5wt%TKX-50 material in Example 1;

[0030] Figure 4 This is a scanning electron microscope (SEM) image of the EMOF-1@10wt%TKX-50 material in Example 2;

[0031] Figure 5 The following are the Fourier Transform Infrared (FT-IR) spectra of the high-stability, high-energy EMOFs materials in Comparative Example 1, Example 1, and Example 2;

[0032] Figure 6 The above are X-ray powder diffraction (PXRD) patterns of the high-stability, high-energy EMOFs materials in Comparative Example 1, Example 1, and Example 2.

[0033] Figure 7Differential scanning calorimetry (DSC) curves of the high-stability, high-energy EMOFs materials in Comparative Example 1, Example 1, and Example 2;

[0034] Figure 8 This is a 3D crystal packing diagram of the EMOF-2 material obtained by SXRD in Comparative Example 2;

[0035] Figure 9 The image shows a scanning electron microscope (SEM) image of the EMOF-2 material in Comparative Example 2.

[0036] Figure 10 This is a scanning electron microscope (SEM) image of the EMOF-2@5wt%NTO material in Example 3;

[0037] Figure 11 This is a scanning electron microscope (SEM) image of the EMOF-2@10wt%NTO material in Example 4;

[0038] Figure 12 The following are the Fourier Transform Infrared (FT-IR) spectra of the high-stability, high-energy EMOFs materials in Comparative Examples 2, 3, and 4;

[0039] Figure 13 The above are X-ray powder diffraction (PXRD) patterns of the high-stability, high-energy EMOFs materials in Comparative Examples 2, 3, and 4.

[0040] Figure 14 Differential scanning calorimetry (DSC) plots of the high-stability, high-energy EMOFs materials in Comparative Examples 2, 3, and 4. Detailed Implementation

[0041] The embodiments of this application will be described in further detail below. Obviously, the described embodiments are only a part of the embodiments of this application, and not an exhaustive list of all embodiments. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of this application can be combined with each other.

[0042] The terms “first,” “second,” etc. (if applicable) in the specification and claims are used to distinguish similar objects and are not necessarily used to describe a particular order or sequence. It should be understood that such data used in this way can be interchanged where appropriate so that the embodiments described herein can be implemented in orders other than those illustrated or described herein. Furthermore, the terms “comprising” and “having,” and any variations thereof, are intended to cover a non-exclusive inclusion, such as a process, method, system, product, or apparatus that comprises a series of steps or units, not necessarily limited to those explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.

[0043] It should be understood that the term "and / or" used in this article is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this article generally indicates that the preceding and following related objects have an "or" relationship.

[0044] Raw materials and equipment:

[0045] (1) Unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in this field.

[0046] (2) The ATRZ used was synthesized according to the literature "Xue Linjun, Tang Zhan, Bi Yangang, et al. Improvement of the synthesis process of 4,4′-azo-1,2,4-triazole [J]. Energetic Materials, 2015, 23(5):420-423." The chemical structural formula of ATRZ (4,4′-azo-1,2,4-triazole) is as follows:

[0047]

[0048] (3) The synthesis of TKX-50 used was carried out according to the literature "Zhu Zhoushuo, Jiang Zhenming, Wang Pengcheng, et al. Synthesis and properties of 5,5′-bitetrazolium-1,1′-dioxanediolam[J]. Energetic Materials, 2014, 22(3):332-336." The chemical structural formula of TKX-50 (5,5′-bitetrazolium-1,1′-dioxanediolam) is as follows:

[0049]

[0050] (4) The NTO used was synthesized according to the literature “Liu Xin, Li Yanan, Chang Pei, et al. Research progress on synthesis and application of NTO and its derivatives [J]. Chemical Propellants and Polymer Materials, 2021, 19(2):18-23.” The chemical structural formula of NTO (3-nitro-1,2,4-triazol-5-one) is as follows:

[0051]

[0052] (5) SEM test: Hitachi S4800 scanning electron microscope was used.

[0053] (6) FT-IR test: A Nicolet Magna IR 560 infrared spectrometer manufactured by Bruker was used.

[0054] (7) PXRD test: Bruker D2 Advance diffractometer manufactured by Bruker was used.

[0055] (8) SXRD test: The Rigaku RAXIS IP diffractometer manufactured by Bruker was used.

[0056] (9) DSC test: A Netzsch DSC-209 differential scanning calorimeter was used.

[0057] (10) True density test: The Accupyc II 1345 fully automated true density analyzer manufactured by Micromeritics was used.

[0058] (11) Explosion test: The Parr 6772 fully automatic oxygen bomb calorimeter manufactured by Parr Corporation was used.

[0059] (12) Impact sensitivity test: The BFH-10 impact sensitivity meter manufactured by Idea Science was used.

[0060] (13) Friction sensitivity test: The FSKM-10 BAM friction sensitivity meter manufactured by Idea Science was used.

[0061] Comparative Example 1

[0062] In this embodiment, EMOF-1 material was prepared according to the following steps:

[0063] (1) Cu(NO3)2·3H2O (242mg, 1mmol) and ATRZ (164mg, 1mmol) were added to 10mL of deionized water, heated, stirred and filtered to obtain clear and transparent Cu(NO3)2 solution and ATRZ solution.

[0064] (2) Cu(NO3)2 solution was slowly added dropwise to a three-necked flask containing ATRZ solution. The mixture was stirred and reacted for 1 hour under a water bath at 55°C. Then, 0.5 mL of 68% concentrated HNO3 solution was added dropwise to the three-necked flask and the reaction was continued for 0.5 hours. After the reaction was completed, the mixture was filtered to obtain a clear and transparent mixed solution.

[0065] (3) Transfer the above-obtained mixed solution to a small glass bottle and add 3 drops of 68% concentrated HNO3 solution to it again. Then let the glass bottle stand at room temperature for 10 days. The blue transparent crystals that precipitate in the bottle are the EMOF-1 material with unadjusted physicochemical properties.

[0066] SXRD tests were performed on the EMOF-1 material, such as... Figure 1 The coordination environment diagram of the EMOF-1 material obtained by X-ray single-crystal diffraction (SXRD) shows that the EMOF-1 is a Cu-based material. 2+ ATRZ is the coordination center ion, and NO3 is the organic ligand.- Energetic metal-organic framework materials for balancing ions. Figure 2 This is a scanning electron microscope (SEM) image of the EMOF-1 material in Example 1.

[0067] The physicochemical properties of EMOF-1 material were characterized, and the results showed that its density was 1.68 g·cm³. -3 The heat of combustion is 4388 kJ·kg⁻¹ -1 Impact sensitivity is 16 J, friction sensitivity is 112 N, and thermal decomposition temperature (heating rate is 15℃·min) is... -1 Shi Ru Figure 7 The temperature is 312.48℃, indicating excellent overall performance.

[0068] Example 1

[0069] The method for preparing EMOF-1@5wt%TKX-50 material is as follows:

[0070] (1) Cu(NO3)2·3H2O (242mg, 1mmol), ATRZ (164mg, 1mmol) and TKX-50 (21.4mg, 0.09mmol) were added to 10mL of deionized water, heated, stirred and filtered to obtain clear and transparent Cu(NO3)2 solution, ATRZ solution and TKX-50 solution;

[0071] (2) Slowly add Cu(NO3)2 solution to a three-necked flask containing ATRZ solution. First, stir the reaction under a water bath at 55°C for 0.5 h, then continue to add TKX-50 solution. After the addition is complete, keep the reaction at the temperature for 1 h.

[0072] (3) Add 0.5 mL of 68% concentrated HNO3 solution to the three-necked flask again, and continue to keep the temperature for 0.5 h. After the reaction is completed, filter to obtain a clear and transparent mixed solution.

[0073] (4) Transfer the above-obtained mixed solution to a small glass bottle, add 3 drops of 68% concentrated HNO3 solution to it again, tighten the bottle cap, and then let the glass bottle stand in a constant temperature oven at 40°C for 14 days. The transparent crystals precipitated in the bottle are the high-stability high-energy EMOFs material, namely the EMOF-1@5wt%TKX-50 material after physicochemical property adjustment.

[0074] FT-IR tests were performed on the EMOF-1@5wt%TKX-50 material after physicochemical property adjustment, such as... Figure 5 As shown, the results indicate that the EMOF-1@5wt%TKX-50 material is a composite of EMOF-1 and TKX-50. The red-blue shift of some infrared peaks and the generation of new peaks may be related to the coordination interaction of TKX-50.

[0075] PXRD tests were performed on the EMOF-1@5wt%TKX-50 material after physicochemical property adjustment, such as... Figure 6 As shown, the results indicate that the EMOF-1@5wt%TKX-50 material after physicochemical property adjustment is consistent with the EMOF-1 material before physicochemical property adjustment, both exhibiting obvious strong diffraction peaks, indicating that the EMOF-1@5wt%TKX-50 material after physicochemical property adjustment still maintains the basic framework structure of the original material.

[0076] SEM tests were performed on the EMOF-1@5wt%TKX-50 material after physicochemical property adjustment, such as... Figure 3 As shown, the results indicate that the EMOF-1@5wt%TKX-50 material after physicochemical property adjustment is basically consistent with the EMOF-1 material before physicochemical property adjustment, both being regular blocky crystals. This shows that the introduction of 5% TKX-50 by mass fraction did not destroy the overall crystal morphology of the EMOF-1 material.

[0077] The physicochemical properties of EMOF-1@5wt% TKX-50 material were characterized. The results showed that its density was 1.72 g·cm⁻³, its heat of combustion was 4790 kJ·kg⁻¹, its impact sensitivity was 14 J, its friction sensitivity was 144 N, and its thermal decomposition temperature (at a heating rate of 15 °C·min⁻¹) was... Figure 7 The temperature was 315.90℃, and the physical and chemical properties changed significantly compared to EMOF-1 material.

[0078] Example 2

[0079] In this embodiment, the TKX-50 in step (1) is replaced by 45.1 mg (0.19 mmol) instead of 21.4 mg (0.09 mmol), and the rest is the same as in Example 1. The product is EMOF-1@10wt% TKX-50 material.

[0080] FT-IR tests were performed on the EMOF-1@10wt%TKX-50 material after physicochemical property adjustment, such as... Figure 5 As shown, the results indicate that the EMOF-1@10wt%TKX-50 material is a composite of EMOF-1 and TKX-50. The red-blue shift of some infrared peaks and the generation of new peaks may be related to the coordination interaction of TKX-50.

[0081] PXRD tests were performed on the EMOF-1@10wt%TKX-50 material after physicochemical property adjustment, such as... Figure 6As shown, the results indicate that the EMOF-1@10wt%TKX-50 material after physicochemical property adjustment is consistent with the EMOF-1 material before physicochemical property adjustment, both exhibiting obvious strong diffraction peaks, indicating that the EMOF-1@10wt%TKX-50 material after physicochemical property adjustment still maintains the basic framework structure of the original material.

[0082] SEM tests were performed on the EMOF-1@10wt%TKX-50 material after physicochemical property adjustment. Figure 4 As shown, the results indicate that the EMOF-1@10wt%TKX-50 material after physicochemical property adjustment is basically consistent with the EMOF-1 material before physicochemical property adjustment, both being regular blocky crystals. This shows that the introduction of 10% TKX-50 by mass fraction did not destroy the overall crystal morphology of the EMOF-1 material.

[0083] Figure 5 The following are the Fourier Transform Infrared (FT-IR) spectra of the high-stability, high-energy EMOFs materials in Comparative Example 1 and Examples 1 and 2. Figure 6 The X-ray powder diffraction (PXRD) patterns of the high-stability, high-energy EMOFs materials in Comparative Example 1 and Examples 1 and 2 show that the intensity of some diffraction peaks in EMOF-1@10wt%TKX-50 and EMOF-1@5wt%TKX-50 materials is inconsistent, which can be attributed to the change in TKX-50 content.

[0084] The physicochemical properties of EMOF-1@10wt%TKX-50 were characterized, and the results showed that its density was 1.77 g·cm³. -3 The heat of combustion is 5226 kJ·kg⁻¹ -1 Impact sensitivity is 15 J, friction sensitivity is 216 N, and thermal decomposition temperature (heating rate is 15 °C / min) is... -1 Shi Ru Figure 7 The temperature was 317.26℃, and its physicochemical properties were significantly different compared to EMOF-1 and EMOF-1@5wt%TKX-50 materials.

[0085] The results of Comparative Example 1 and Examples 1 and 2 demonstrate that, based on the structural characteristics and performance advantages of high-energy explosives, molecular high-nitrogen energetic compounds and ionic high-nitrogen energetic salts are important components of high-energy explosives. Molecular high-nitrogen energetic compounds contain a large number of N-N and CN bonds in their molecular structure, exhibiting a high positive enthalpy of formation, and their high nitrogen and low carbon-hydrogen content facilitates oxygen equilibrium. Ionic high-nitrogen energetic salts, with high-nitrogen heterocyclic energetic anions as their core framework, are widely used in energetic applications due to their lower vapor pressure and higher density compared to high-nitrogen energetic compounds. Introducing them as molecular modifiers into EMOF materials is of great significance for regulating the physicochemical properties of EMOF materials. This method successfully achieved the regulation of the energy characteristics and stability of EMOF-1 materials while simultaneously preserving their complete framework structure.

[0086] Comparative Example 2

[0087] In this embodiment, Cu(NO3)2·3H2O in step (1) was replaced with Co(BF4)2 (233 mg, 1 mmol), and the rest was the same as in Example 1. The resulting pale red transparent crystals were EMOF-2 materials with unadjusted physicochemical properties.

[0088] SXRD tests were performed on the EMOF-2 material, such as... Figure 8 As shown, its 3D crystal packing diagram indicates that the EMOF-2 is a Co-based... 2+ ATRZ is the coordination center ion, BF4 is the organic ligand. - Energetic metal-organic framework materials for balancing ions. Figure 9 The image shows a scanning electron microscope (SEM) image of the EMOF-2 material in Comparative Example 2.

[0089] The physicochemical properties of EMOF-2 were characterized, and the results showed that its density was 1.64 g·cm³. -3 The heat of combustion is 4223 kJ·kg⁻¹ -1 Impact sensitivity is 15J, friction sensitivity is 120N, and thermal decomposition temperature (heating rate is 15℃·min) is... -1 Shi Ru Figure 14 The temperature is 319.09℃, indicating excellent overall performance.

[0090] Example 3

[0091] In this embodiment, Cu(NO3)2·3H2O in step (1) is replaced with Co(BF4)2 (233mg, 1mmol), TKX-50 is replaced with NTO (20.9mg, 0.16mmol), and the rest is the same as in Example 1. The product is EMOF-2@5wt%NTO material.

[0092] FT-IR tests were performed on the EMOF-2@5wt%NTO material after physicochemical property adjustment, such as... Figure 12 As shown, the results indicate that the EMOF-2@5wt%NTO material is a composite of EMOF-2 and NTO. The red-blue shift of some infrared peaks and the generation of new peaks may be related to the coordination interaction of NTO.

[0093] PXRD tests were performed on the EMOF-2@5wt%NTO material after physicochemical property adjustment, such as... Figure 13 As shown, the results indicate that the EMOF-2@5wt%NTO material after physicochemical property adjustment is consistent with the EMOF-2 material before physicochemical property adjustment, both exhibiting obvious strong diffraction peaks, indicating that the EMOF-2@5wt%NTO material after physicochemical property adjustment still maintains the basic framework structure of the original material.

[0094] SEM tests were performed on the EMOF-2@5wt%NTO material after physicochemical property adjustment. Figure 10 As shown, the results indicate that the EMOF-2@5wt%NTO material after physicochemical property adjustment is basically consistent with the EMOF-2 material before physicochemical property adjustment, both being large lamellar crystals, indicating that the introduction of 5% NTO by mass fraction did not destroy the overall crystal morphology of the EMOF-2 material.

[0095] The physicochemical properties of EMOF-2@5wt%NTO were characterized, and the results showed that its density was 1.67 g·cm³. -3 The heat of combustion is 4564 kJ·kg⁻¹ -1 Impact sensitivity is 15J, friction sensitivity is 252N, and thermal decomposition temperature (heating rate is 15℃ / min) is... -1 Shi Ru Figure 14 The temperature was 333.01℃, and the physicochemical properties changed significantly compared to EMOF-2 material.

[0096] Example 4

[0097] In this embodiment, Cu(NO3)2·3H2O in step (1) is replaced with Co(BF4)2 (233mg, 1mmol), TKX-50 is replaced with NTO (44.1mg, 0.33mmol), and the rest is the same as in Example 2. The product is EMOF-2@10wt%NTO material.

[0098] FT-IR tests were performed on the EMOF-2@10wt%NTO material after physicochemical property adjustment, such as... Figure 12As shown, the results indicate that the EMOF-2@10wt%NTO material is a composite of EMOF-2 and NTO. The red-blue shift of some infrared peaks and the generation of new peaks may be related to the coordination interaction of NTO.

[0099] PXRD tests were performed on the EMOF-2@10wt% NTO material after physicochemical property adjustment, such as... Figure 13 As shown, the results indicate that the EMOF-2@10wt%NTO material after physicochemical property adjustment is consistent with the EMOF-2 material before physicochemical property adjustment, both exhibiting obvious strong diffraction peaks, indicating that the EMOF-2@10wt%NTO material after physicochemical property adjustment still maintains the basic framework structure of the original material.

[0100] SEM tests were performed on the EMOF-2@10wt%NTO material after physicochemical property adjustment, such as... Figure 11 As shown, the results indicate that the EMOF-2@10wt%NTO material after physicochemical property adjustment is basically consistent with the EMOF-2 material before physicochemical property adjustment, both being large lamellar crystals, indicating that the introduction of 10% NTO by mass did not destroy the overall crystal morphology of the EMOF-2 material.

[0101] Figure 12 The following are the Fourier Transform Infrared (FT-IR) spectra of the high-stability, high-energy EMOFs materials in Comparative Example 2, Example 3, and Example 4. Figure 13 The X-ray powder diffraction (PXRD) patterns of the high-stability, high-energy EMOFs materials in Comparative Example 2, Example 3, and Example 4 show that the intensity of some diffraction peaks in EMOF-2@10wt%NTO and EMOF-2@5wt%NTO materials is inconsistent, which can be attributed to the change in NTO content.

[0102] The physicochemical properties of EMOF-2@10wt%NTO were characterized, and the results showed that its density was 1.67 g·cm³. -3 The heat of combustion is 5066 kJ·kg⁻¹ -1 Impact sensitivity is 16 J, friction sensitivity is 288 N, and thermal decomposition temperature (heating rate is 15℃·min) is... -1 Shi Ru Figure 14 The temperature was 336.32℃, and its physicochemical properties were significantly different compared to EMOF-2 and EMOF-2@5wt%NTO materials.

[0103] The above results show that the method described in this embodiment successfully modulates the energy properties and stability of EMOF-2 materials while preserving their complete framework structure.

[0104] Based on the data from the comparative examples and embodiments above, and according to the test results of density, heat of combustion, impact sensitivity, friction height, and thermal decomposition temperature, the high-stability, high-energy EMOFs material has the potential to be used as a heat-resistant, insensitive explosive.

[0105] This invention utilizes TKX-50 and NTO as high-energy molecular modifiers to achieve physicochemical property modulation of EMOF materials through in-situ synthesis. The method is simple, safe, and efficient. The resulting physicochemically modified EMOF materials maintain the integrity of the original EMOF framework structure while effectively improving their energy characteristics and stability. This provides a novel research approach for the modification of metal-organic framework energetic materials and has broad application prospects.

[0106] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. For those skilled in the art, other variations or modifications can be made based on the above description. It is impossible to exhaustively list all the implementation methods here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing a highly stable, high-energy EMOF material, characterized in that, Includes the following steps: S01: Add the raw materials to the solvent separately, heat and stir until completely dissolved, filter, and obtain the raw material solutions respectively; The raw materials include metal ion salts, azole-rich ligands, and high-energy molecular modifiers; the high-energy molecular modifiers include one of 5,5′-bitetrazol-1,1′-dioxohydroxyammonium salt and 3-nitro-1,2,4-triazol-5-one; the metal ion salts include one of Cu(NO3)2, Cu(BF4)2, CuSO4, Co(NO3)2, Co(BF4)2, CoCl2, Zn(NO3)2, Zn(BF4)2, ZnSO4, Fe(NO3)2, FeSO4, FeCl2, Ni(NO3)2, NiCl2, and their corresponding metal ion salt hydrates; the azole-rich ligand is 4,4′-azo-1,2,4-triazole; The raw material solution comprises a metal ion salt solution, a nitrogen-rich azole ligand solution, and a high-energy molecular modulator solution; the concentration of the metal ion salt solution is greater than or equal to 1.5 mg·mL. -1 ; S02: Mix the raw material solutions in the mixing order, stir, add strong acid solution dropwise for the first time, stir at constant temperature, filter, and obtain a clear and transparent mixed solution; S03: Transfer the clear and transparent mixed solution to the reaction device, add a strong acid solution dropwise for the second time, then seal the reaction device in a constant temperature oven and let it stand. The precipitated transparent crystals are the high-stability, high-energy EMOFs materials.

2. The method for preparing high-stability, high-energy EMOFs materials according to claim 1, characterized in that, The solvent is one of deionized water, methanol, ethanol, acetonitrile, acetone, ethyl acetate, and dichloromethane.

3. The method for preparing high-stability, high-energy EMOFs materials according to claim 1, characterized in that, The mixing sequence in step S02 is as follows: first, mix the metal ion salt solution and the nitrogen-rich azole ligand solution, then add the high-energy molecular regulator solution; stir at 30~70°C for 1~3h, add the strong acid solution dropwise for the first time, and stir at a constant temperature for 0.5~2h. The settling conditions in step S03 are settling at 20~60°C for 7~14 days.

4. The method for preparing high-stability, high-energy EMOFs materials according to claim 1, characterized in that, The strong acid solution is one of 38% concentrated HCl, 98% concentrated H2SO4, and 68% concentrated HNO3.

Citation Information

Patent Citations

  • Two-dimensional energetic CMOFs material containing nitro nitrogen-rich heterocyclic anions and preparation method of two-dimensional energetic CMOFs material

    CN112552520A

  • Hectogram-scale solution crystallization method for preparing [Ba(BTO)(H2O)]n barium-based energetic metal organic frameworks

    CN112592482A